PERAN SATUAN PENGAWASAN INTERNAL DAN DEWAN PENGAWAS TERHADAP TERWUJUDNYA GOOD UNIVERSITY GOVERNANCE DENGAN CONTROL ENVIRONMENT DAN AUDIT RISK SEBAGAI VARIABEL MODERATING (STUDI EMPIRIS PADA PERGURUAN TINGGI SATKER BADAN LAYANAN UMUM DIINDONESIA) - Khairunnisa, Novita; Rasuli, M.; Ratnawati, Vince (Jurnal Ekonomi, 2016)
This research intends to analyze the role Internal Audit and Board OfSupervisors to reached Good University Governance, and analyze the roleControl Environment and Audit Risk in mediate their relationship to GoodUniversity Governance. The object of this research is internal auditors andDewan Pengawas. This research was conducted to 60 Universities unit BLU inIndonesia. Analyctical model which used for this research to ModeratedRegression Analysis (MRA). Based on research concluded that Internal Audit andBoard Of Supervisors could affect the Good University Governance. It can beproven by the first and the fourth hypothesis. And then, control environment andaudit risk proved to mediate role Internal Audit and also role Board OfSupervisors toward Good University Governance. It can be proven by the second,third, fifth, and the sixth hypothesis.